Bank loans for private and public firms in a credit crunch - Jason Allen; Teodora Paligorova (Bank of Canada, 2011)
Banks reliance on short-term funding has increased over time. While an effective source of financing in good times, the 2007 financial crisis has exposed the vulnerability of banks and ultimately firms to such a liability structure. The authors show that banks that relied most on wholesale funding were the ones to contract its lending the most during the crisis. Their results suggest that banks propagate liquidity shocks by reducing credit only to a certain type of borrower. Importantly, in the financial crisis banks passed the liquidity shock only to public firms. Furthermore, long-term relationships between firms and banks played an important role during the crisis. Public firms with weak banking relationships pre-crisis experienced a greater credit crunch than other public borrowers.
Keywords: G01; G20; 330; Financial institutions